Brimonidine related acute follicular conjunctivitis: Onset time and clinical presentations, a long-term follow-up. Issue 29 (23rd July 2021) - Yeh, Po-Han; Cheng, Yu-Chun; Shie, Shian-Sen; Lee, Yung-Sung; Shen, Su-Chin; Chen, Henry Shen-Lih; Wu, Wei-Chi; Su, Wei-Wen
Abstract : Abstract: To evaluate the duration of topical brimonidine therapy before the onset of brimonidine-related allergic conjunctivitis and the clinical characteristics associated with the development of brimonidine allergy. We retrospectively enrolled patients who presented brimonidine allergy from December 1, 2008 to November 30, 2020. The duration of brimonidine treatment, concomitant medications, benzalkonium chloride (BAK) exposure, change in IOP, and season of onset were evaluated. 292 patients were included, among which 147 were female and 145 were male. The mean age was 58.3 ± 13.6 years old. The mean (median) duration of brimonidine therapy was 266.6 (196) days, with a peak at 60–120 days. The duration was similar whether the patients received brimonidine monotreatment or in combination with other glaucoma drugs, with or without BAK. The IOP increased by 5.6% after brimonidine allergy ( P < .001), which was even higher in the brimonidine monotherapy group (9.2%, P < .001). There was no significant IOP elevation in patients treated with multiple glaucoma medications. Around half of brimonidine allergy occurred within 6 months, with a peak in 2 to 4 months. The duration did not differ in patients receiving brimonidine monotherapy or multiple glaucoma medications. The presence of BAK did not affect the duration either. When brimonidine allergy occurred, there was a loss of IOP control, especially in patients receiving brimonidine monotherapy. It is recommended to switch to other types of glaucoma medications for better IOP control.